الإمام الساعاتي ومنهجة في كتابية "بدائع المنن في جمع وترتيب مسند الشافعي والسنن" و "القول الحسن شرح بدائع المنن" : دراسة تحليلية - Nunun Zainun Bt Ahmad Hidayat
Imam Ahmad ibn Abdul Rahman al-Banna al-Sa’ati (d. 1300-1378AH or 1882-1958M)was amongst the prominent hadith scholars in the 20th century in Egypt. As a prolific author, he had written a number of important works, many of which are in the field of hadith and its studies such as “Badai’ al-Minan fi Jam’I wa Tartib Musnad al-Shafi’I wa al-Sunan”, al-Qawl al-Hasan Syarh Badai’ al-Minan” and others. However,this influential figure and his works in hadith have yet to receive serious attention by the academics as subjects of studies. Thus, this thesis aims to discuss certain aspects of his life and life and his works on hadith.More specifically, it focuses on analysing his methods in compilation,arrangement and commentary based on two of his works, which are “Badai’ al-Minan fi Jam’I wa Tartib Musnad al-Shafi’I wa al-Sunnan” and al-Qawl al-Hasan Syarh Badai’ al-Minan”. The study employs the relevant methods of qualitative research including historical, deductive and textual analysis.The findings of the study indicate, among others, the important role of al-Sa’ati in compiling together the Musnad of al-Shafi’I and Sunan of al-Shafi’I as a major source of the Shafi’ite School of Jurisprudence.He had also arranged the hadiths of the books into detailed chapters in jurisprudence and provided some forms of commentaries and legal discussions so asa to facilitate its usage amongst the readers. In addition,he had also added hadiths narrated by other hadith scholars so as to further strengthen the status of some of the hadiths in the books.